Investigating Tup1-Cyc8 complex function in Saccharomyces cerevisiae following the confirmation and characterization of a TUP1 conditional mutant - Agarwal, Pranay (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2023)
The Tup1-Cyc8 complex is a well-defined corepressor complex found in S. cerevisiae. It is known to regulate close to 3% of all yeast genes and has orthologs reported in mammals. Its exact functioning is not well-understood. Here we use a conditional TUP1 mutant of S. cerevisiae to perform time-course analysis of the events leading to Tup1-Cyc8 target gene derepression and assess the advantages of this mutant compared to a conventional tup1 deletion mutant. To prepare the conditional mutant, the protein of interest (Tup1p) was first tagged with an FRB tag. The conditional mutants strain also contains the ribosomal protein RPL13A, fused with FKBP12, which binds to FRB in the presence of rapamycin. This leads to the FRB-tagged protein being `Anchored-away? from the nucleus on the addition of rapamycin. The FRB tag was confirmed with a Western blot. The cells of the anchor-away strain acquired a flocculant phenotype at two hours post-rapamycin addition, a phenotype governed by the FLO family of genes. The FLO1 gene was derepressed at 2 hours post-rapamycin addition and the SUC2 gene at 40 minutes in the anchor away strains. SED1 was unaffected while PMA1, which is a housekeeping gene, maintained a stable transcription in all the strains. A ChIP assay following the Tup1p anchor away (Tup1-AA) time course showed that RNA Polymerase II levels correlated well with the transcription in the FLO1 and SUC2 genes. To study the occupancy of Cyc8p in the Tup1-AA strain, a modified Tup1-AA strain containing a 9-myc tagged Cyc8p (Cyc8-myc) was used, since a ChIP grade antibody for Cyc8p was unavailable. At the FLO1 promoter following Tup1-AA, Tup1p levels declined while the detection of Cyc8-myc increased with time. However, Tup1p and Cyc8-myc were not detected at the repressed SUC2 promoter, suggesting that the epitopes of both proteins may have been masked by the presence of other factors at this gene. Together, the Tup1-AA strain revealed that although Tup1p is lost from the FLO1 promoter following Tup1p anchor-away, Cyc8p persists where it could contribute independently to FLO1 gene repression.
APPROVED
Keywords: Tup1-Cyc8; Anchor-away; Derepression; Saccharomyces cerevisiae; Conditional mutant; ChIP; RT-qPCR; Gene expression; Protein occupancy